Factors influencing customer satisfaction and loyalty in Sharia-compliant hotels in Yogyakarta, Indonesia - Suhud, Diar Melati; Andriansyah, Yuli; Putra, Bintang Paula (Journal of Islamic Economics Lariba, 2023)
IntroductionSharia-compliant hospitality is gaining prominence globally, particularly in Indonesia, where Islamic values increasingly influence consumer preferences. Despite the growing demand for Sharia-compliant hotels, research on the factors driving customer satisfaction and loyalty in this niche remains limited.ObjectivesThis study investigates the relationships between key factors—self-satisfaction, aesthetics, price, prestige, transactional value, hedonic value, and quality—and customer satisfaction and loyalty in Sharia-compliant hotels in Yogyakarta. It aims to identify which factors most significantly impact these constructs and how satisfaction translates into loyalty.MethodThe study employed a quantitative approach, collecting data from 113 customers of three Sharia-compliant hotels in Yogyakarta using a structured questionnaire. Structural Equation Modeling (SEM) was used to analyze the relationships among variables and test hypotheses.ResultsThe findings revealed that self-satisfaction, price, transactional value, hedonic value, and quality significantly enhance customer satisfaction, while satisfaction strongly predicts loyalty. Aesthetics and prestige, however, did not exhibit significant effects. These results suggest that customers prioritize adherence to Islamic principles, fair pricing, and service quality over visual appeal or social status.ImplicationsThe study underscores the importance of integrating Sharia principles with high-quality services and transparent transactions to meet customer expectations and foster loyalty. It provides actionable insights for practitioners seeking to differentiate their offerings in the competitive Islamic hospitality sector.Originality/NoveltyThis study contributes to the body of knowledge on Islamic hospitality by integrating service quality frameworks with Sharia principles, offering a nuanced understanding of customer satisfaction and loyalty in this context.